1998
DOI: 10.1161/01.cir.98.18.1848
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinemia After an Oral Methionine Load Acutely Impairs Endothelial Function in Healthy Adults

Abstract: Background-Elevated plasma homocysteine is a risk factor for arteriosclerosis, but a cause-and-effect relationship remains to be fully established. Endothelial dysfunction, an early event in the atherogenic process, has been shown to be associated with hyperhomocysteinemia in experimental and human studies. To further establish a direct relationship between changes in plasma homocysteine and endothelial dysfunction, we investigated whether moderate hyperhomocysteinemia induced by an oral methionine load would … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
169
4
3

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 319 publications
(192 citation statements)
references
References 31 publications
16
169
4
3
Order By: Relevance
“…This agrees with interventional (De Jong et al, 1999b;Peterson and Spence, 1998;Vermeulen et al, 2000) and experimental (Bellamy et al, 1998;Durand et al, 1996bDurand et al, , 1997aLentz et al, 1996) investigations that suggest a causal relationship between elevated homocysteine levels and vascular spasm and thrombosis and with cross-sectional studies, which suggest that elevated homocysteine levels contributed to acute fatal thromboembolic events (Alfthan et al, 1997;Nygård et al, 1997a). Hyperhomocysteinemia, when detected under basal conditions, was found to be related to recurrent and/or premature (Falcon et al, 1994) venous thrombosis in subjects less than 40 years old.…”
Section: Hyperhomocysteinemia: An Independent Risk Factor For Thrombosissupporting
confidence: 86%
See 1 more Smart Citation
“…This agrees with interventional (De Jong et al, 1999b;Peterson and Spence, 1998;Vermeulen et al, 2000) and experimental (Bellamy et al, 1998;Durand et al, 1996bDurand et al, , 1997aLentz et al, 1996) investigations that suggest a causal relationship between elevated homocysteine levels and vascular spasm and thrombosis and with cross-sectional studies, which suggest that elevated homocysteine levels contributed to acute fatal thromboembolic events (Alfthan et al, 1997;Nygård et al, 1997a). Hyperhomocysteinemia, when detected under basal conditions, was found to be related to recurrent and/or premature (Falcon et al, 1994) venous thrombosis in subjects less than 40 years old.…”
Section: Hyperhomocysteinemia: An Independent Risk Factor For Thrombosissupporting
confidence: 86%
“…It has also been reported that homocysteine level is related to the extent of atherosclerosis in coronary and peripheral arteries (Chao et al, 1999b;van den Berg et al, 1996;Verhoef et al, 1997b;von Eckardstein et al, 1994). Third, as we will detail below (see "Potential Pathogenic Mechanisms of Hyperhomocysteinemia"), our own work (Durand et al, 1997a) and the work of Lentz et al (1996) and Bellamy et al (1998) give experimental evidence that moderate hyperhomocysteinemia, which leads to vascular dysfunction, might increase the cardiovascular risk independently of other risk factors.…”
Section: Hyperhomocysteinemia: An Expected Causal Risk Factor For Athsupporting
confidence: 53%
“…This is difficult to reconcile with previous report that changes in homocysteine level had significant effect on peripheral vascular reactivity [10]. However, this finding is in agreement with previous results of the change in cerebral blood flow velocities after a standardized methionine challenge.…”
Section: Discussionsupporting
confidence: 71%
“…Folate is the principal therapy in patients with hyperhomocysteinaemia because it is the cosubstrate for the homocysteine-metabolizing enzyme methionine synthase. Hyperhomocysteinaemia is known to be associated with impaired endotheliumdependent vasodilation [36,37]. Plasma homocysteine concentrations were, however, lower in the diabetic than in the control rats, as described previously [38], and were not influenced by treatment with 5-MTHF.…”
Section: Basalsupporting
confidence: 68%